ANALISIS PEMBIAYAAN IJARAH PADA PERBANKAN SYARIAH - Almirah Luthfiyah Nur Aurellia; Fauzatul Laily Nisa (CV. KAMPUS AKADEMIK PUBLISHING, 2024)
. This research was conducted with the aim of analyzing the application of financing using the Ijarah (rental) scheme in the sharia banking industry. The theories underlying this research include the concept of ijarah itself, the Ijarah financing mechanism, the fatwa of the National Sharia Council of the Indonesian Ulema Council (DSN-MUI) regarding Ijarah, as well as the application and implementation of Ijarah financing in practice. This research is descriptive qualitative research carried out in 2016, using data collection methods in the form of literature studies. The research results show that financing products in Islamic banks based on the leasing principle include two types, namely pure lease (Ijarah) and termination of lease with transfer of asset ownership known as Ijarah Muntahiya Bittamlik (IMBT). IMBT is basically a combination of a rental agreement and a sale and purchase agreement.